Sparking conversations: Research supports rethinking of agricultural withholding tax proposition in Kenya - Omune, Lensa; Mbuthia, Juneweenex; Thurlow, James; Diao, Xinshen; Breisinger, Clemens; Ngugi, Rose; Laichena, Joshua; Malot, Kenneth; Shibia, Adan (CGIAR System Organization, 2024)
Since September 2022, the government of Kenya has been implementing policy measures under its “Bottom-Up Transformation Agenda (BETA)”. Alongside measures aimed at promoting economic recovery and improving livelihoods, the government is also redesigning revenue mobilization instruments geared towards fiscal consolidation and supporting economic growth. These interventions have already yielded some progress. For example, the latest GDP report indicates that Kenya’s economy grew by 5.9 percent in the third quarter of 2023 – up from 4.3 percent in the same quarter in 2022.